Document semantics: Two approaches - Ramalho, José Carlos (1996)
SGML introduced DTD idea to formally describe document syntax and structure. One of its main characteristics is the fact of being purely declarative and fully independent of the future document's processing (typesetting, formatting, translation/transformation). In this context, SGML has become the international standard to be followed. Sooner or later, a document has to be processed. In order to do that we need to associate semantics to the document's structure. In a compiler context, normally we separate semantics in two, static and dynamic. Establishing a parallelism with document processing, we can think of the document's decorated tree (as recognized by a SGML analyzer) as being the static semantics and document's tree transformation and/or reaction as dynamic semantics. Pursuing this idea, we will present and discuss a study of the relationship between SGML, DAST (Decorated Abstract Syntax Tree), and Algebraic Specification tools, in order to better understand how to formally process documents in general and how to specify and build generic document processing tools.